An overview of patellofemoral pain—from a tissue homeostasis perspective - Dye, Scott F.; Dye, Christopher C. (Annals of Joint; Vol 3 (July 2018): Annals of Joint, 2018)
The etiology of patellofemoral pain (PFP) has been misunderstood for decades, leading to the broad acceptance of therapies that are not only ineffective, but often harmful. The solution to the problem of PFP eventually came from the discovery and development of a new musculoskeletal paradigm: tissue/joint homeostasis. This new conceptualization of the cause of anterior knee pain (AKP) looks beyond the mere structural, anatomic and biomechanical factors, deeper into the underlying perturbed biology. Loss and restoration of tissue homeostasis of innervated PF components such as synovium and bone, best accounts for the symptoms of PFP, independent of factors such as chondromalacia patella, or patellofemoral (PF) “malalignment”.